USING REFLECTIVE EDUCATIONAL TECHNOLOGIES IN DEVELOPING STUDENTS’ PROFESSIONAL COMPETENCIES (Ustozlar uchun, 2025)
This article examines the issues of developing students’ professional competencies through the use of reflective educational technologies in higher education institutions. The study analyzes the theoretical foundations of the reflective approach, its pedagogical significance, and its role in fostering students’ self-analysis, self-evaluation, and professional development-oriented thinking skills. In addition, the possibilities of enhancing students’ professional preparedness through the integration of reflective methods into the educational process are highlighted.